Online-business in Afghanistan, current trend and challenges ahead: A conceptual study / Abdul Fareed Delawari. - Delawari, Abdul Fareed (Universiti Teknologi Mara Selangor, 2019)
This is a conceptual paper about the current trend and challenges of online business in Afghanistan. Since more than 10% of the population in Afghanistan has access to the internet, some businesses materialize this opportunity and offer a variety of products online in the capital and some other big cities. The author has found that these businesses are formed based on Cash on Delivery Model (COD). Identified challenges of online businesses such as lack of opportunity entrepreneurs, security, low purchasing power, corruption, lack of infrastructure and regulatory initiatives, house addressing, IT literacy and social trust as well as internet accessibility have been discussed in three different but interconnected concepts namely; entrepreneurs, government and society.